Contagious infections in competitive sports - Eichner, E. R. (1995)
1. Exercise can change blood levels, proportions, and functions of white blood cells, especially natural killer cells. These changes are generally modest and brief, but they may have clinical importance. 2. Whether exercise helps or harms immunity or increases the chance of acquiring upper respiratory tract infection (URTI) or other infections is still debated, but may depend on the stress level involved. 3. The risk today of contracting HIV through competitive sports is next to zero, although a theoretical risk exists for wrestling and certain other "blood sports." 4. Prevention of infections among athletes hinges on common sense, good hygiene, prudent immunization, wise training, and "universal precautions." 5. A practical gauge for the athlete with URTI is the "neck check," wherein symptoms below the neck should preclude strenuous exercise, whereas those above the neck may be less serious.